Emergent use of retrograde left ventricular support in patients after transcatheter aortic valve replacement. Issue 2 (16th November 2012) - Martinez, Claudia A.; Singh, Vikas; Heldman, Alan W.; O'Neill, William W.
<x xml:space="preserve">Abstract</x> Transcatheter aortic valve replacement (TAVR) is currently a therapeutic alternative to open aortic valve replacement for high‐risk patients with severe symptomatic aortic valve stenosis. The procedure is associated with some life‐threatening complications including circulatory collapse which may require temporary hemodynamic support. We describe our experience with the use of the Impella 2.5 system to provide emergent left ventricular support in cases of hemodynamic collapse after TAVR with the Edwards SAPIEN prosthesis.© 2012 Wiley Periodicals, Inc.